Identitas Visual Kementerian BUMN sebagai Upaya Membangun Citra - Lianto, Gwyneth Eveline; Budiwaspada, Agung Eko (Serat Rupa: Journal of Design, 2024)
The increasingly advanced development of information technology offers new challenges and opportunities for industries in Indonesia. In an effort to survive and respond to increasingly fierce global competition, it is necessary to develop a strong and adaptive identity and image. The Ministry of State-Owned Enterprises (known as Kementerian Badan Usaha Milik Negara or “BUMN”) is an institution engaged in the national economy based on economic democracy. The launching of BUMN's new visual identity is a progressive symbol of modern change. Visual identity is an important consideration in building good branding. To face the new era and form a trusted brand image for partners and the public, BUMN decided to create a new visual identity in tandem with institutional restructuring and reform. This article will examine the new visual identity as a result of BUMN’s rebranding and its role in the process of building a new image for BUMNs. Based on the formulation of the problem, the research aims to understand the visual identity of BUMNs and its role in the process of building a new image that is progressive towards changing times and is more trusted as an Indonesian national economic institution. The research is expected to contribute to understanding how visual identity shapes the process of building the image of BUMNs.